La empresa: enemigo público n° 1 - Berckemeyer, Fernando (2019)
Since the publication of the theory of capitalism by Karl Marx, in the early 1860s,companies and entrepreneurs have been seen as public enemies by a part of society; when, in fact, they are not. This essay explains how economic freedom has managed to lead the world into levels of progress unprecedented in history, decreasing poverty rates, and improving the quality of life of human beings. However, economic inequality remains in the capitalist world, and it has even increased in some times and regions; and with it, the belief that such inequality generates poverty. But this is mere confusion, for it is not the case. There is no serious empirical study proving a causal relationship between income disparity and poverty, while, point in fact, there are many concrete examples proving the contrary.